IMPLEMENTASI DAKWAH DALAM PENINGKATAN KESADARAN HUKUM - Ilham Ilham (IAIN Palopo, 2009)
Da’wah and law have a tight correlation since da’wah is an effort to bring human beings to the right way which based on religious and morality norms. Therefore, human beings are subject and object of law. In order to increase the understanding to the low, da’wah has an important role as a medium. In this regard, human beings need a law the reserve and save the right as a honorable person (muhtaram). The activities of da’wah must be functional and has a transformative role in facing a social change.